Analysis of nifH-RNA reveals phylotypes related to Geobacter and Cyanobacteria as important functional components of the N2-fixing community depending on depth and agricultural use of soil - Calderoli, Priscila A. (2017)
Fil: Calderoli, Priscila A. Universidad Nacional de La Plata; Argentina.